QUANTITATIVE EVALUATION OF BUFFALO SEMEN BY CASA DURING CRYOPRESERVATION PROCESS - KUMAR, DHARMENDRA; KUMAR2, PRADEEP; YADAV, P s (The Indian Journal of Animal Reproduction, 2016)
The present study evaluated the quantitative impact of cryopreservation on buffalo bull sperm with the use ofcomputer assisted semen analyzer (CASA). The motility and kinetics parameters were not affected during equilibration(p>0.05), except curvilinear velocity (VCL), average lateral head displacement and viability, but total motility(83.07±0.57%), progressive motility (47.56±0.70%) and rapid motility (64.17±1.17%) of fresh semen reduced to57.41±0.92%, 23.56±0.60% and 30.47±0.88%, respectively in frozen-thawed semen (p
Keywords: CASA; Semen; Sperm motility; Sperm kinetics; Viability